The role of financial intelligence quotient and financial literacy for paving a path towards financial well-being - Miečinskienė, Algita; Stankevičienė, Jelena; Jurevičienė, Daiva; Taujanskaitė, Kamilė; Danilevičienė, Irena; Gudelytė-Žilinskienė, Laura (Journal of Business Economics and Management, 2023)
This study aims to develop an original financial intelligence quotient (FIQ) measurement conceptual model, including guidelines for adequately handling personal finances in four developed areas to serve as benchmarks of financial intelligence. Four hypotheses were raised, one of them consists of four parts. Methods used: a questionnaire to determine how well a person’s financial decisions comply with financial behaviour guidelines, Cronbach’s Alpha coefficient to determine the internal consistency of the scales used in the questionnaire, Spearman correlation coefficient to determine the linear dependence between the variables, a linear regression model was developed to substantiate the hypothesis, the MannWhitney-Wilcoxon rank-sum criterion, the KolmogorovSmirnov test to choose the data distribution according to the normal distribution, descriptive statistics, the Kruskal-Wallis test to support the hypothesis. The results show that an individual’s FIQ influences financial decision-making in essential areas of personal finance management and varies due to education but is not dependent on gender and age. Research limitations: The study focuses only on FI and its impact on the economic well-being of Lithuanian students; the study uses oneyear data; data sets for different age groups were not the same size; and the data was not distributed in groups according to the normal distribution.